Potensi Proteolitik Isolat Bakteri Fictibacillus barbaricus Asal Pantai Papuma Kabupaten Jember - Diva Amy Laila Nur Amalia (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Exploration of marine bacteria as producers of therapeutic proteins, such as protease enzymes, is still very limited. One potential bacterium that has not been widely studied is Fictibacillus barbaricus, especially those from marine waters. This study was conducted to determine the proteolytic potential of bacterial isolates of F. barbaricus from the waters of Papuma Beach, Jember Regency, and its biochemical characterization. Confirmation of isolates was done through morphological characterization. Proteolytic potential is known through a series of proteolytic tests using skim milk agar (SMA) media, followed by protein extraction, measurement of protein concentration using the Bradford method, and proteolytic tests on crude protein. Biochemical characterization includes catalase test, starch hydrolysis, nitrate reduction, citrate utilization, and glucose fermentation. Characterization results showed a round colony shape, whitish yellow, irregular edge and flat edge. F. barbaricus is Gram-positive and able to produce endospores. Determination of proteolytic activity of bacterial isolates of F. barbaricus showed positive results with a proteolytic index (IP) of 0.47 ± 0.13 colonies clasified to the low proteolytic activity, and the IP value of crude protein was 2.94 ± 0.32 which was classified as a medium proteolytic activity. Measurement of crude extract concentration of F. barbaricus showed a value of 1.83 ± 0.97 and was known to be greater than the control bacteria. In addition, biochemical characterization showed diverse enzyme profiles including positive catalase and starch hydrolysis, negatif nitrate reduction and citrate utilization, and carbohydrate fermentation test results that could not be interpreted. These results indicate the potential for further application in the field of biotechnology. This research is expected to increase knowledge about the potential and utilization of marine F. barbaricus as a source of therapeutic protein.
Reaploud Repository February_Hasyim
Keywords: Fictibacillus barbaricus; proteolytic; marine bacteria; biochemical characterization; therapeutic protein